Determining the parameters of quantitative-qualitative runoff model for Shushtar city using SWMM calibration - Behzad Jamshidi; Yaser Tahmasebi birgani; Mohammad Jafarpour; NadAli Alavi Bakhtiarvand; Ali Akbar Babaei; Ali Haghighi; Gholamreza Goudarzi (Mashhad University of Medical Sciences, 2020)
Background and purpose: Increasing population and urbanization density and as a result increasing impermeable levels, led to an increase in the volume of urban runoff. Applying simulation models is a suitable way to know the amount of runoff quality parameters. This study aims at evaluating the quality of urban runoff in Shushtar city using storm water management model (SWMM). Materials and Methods: Two given rainfall events in 1395 for calibration and validation of the model were considered. The parameters related to the first rainfall event were measured at the outlet of the urban drainage system. Quantitative and qualitative calibration of the model was performed using the first rainfall and model validation was performed using the second rainfall. Results: In the hydraulic calibration, mean values of impermeability, slope, catchment width and manning coefficient were estimated to be 50%, 75%, 25 m and 0.013, respectively. In the qualitative calibration, the coefficients of the Build-up equations for TSS, COD and Zn were equal to 95-25, 48-1, 1- 0.09, respectively. The coefficients of Wash-off equations for TSS, COD and Zn were estimated 0.21- 0.8, 0.2-0.8 and 0.19-0.78, respectively. Conclusion: The results showed that the accurate calibration of the model enhances the ability of the model to estimate the quantitative and qualitative parameters in future rainfall events for the study area. According to the results, the modeling is a powerful tool that can be very useful to improve runoff management.